Book publishing and AI – a help or a hindrance? - PEACE, Katie (Institutional Knowledge at Singapore Management University, 2023)
With the emergence of ChatGPT into the public consciousness in late 2022, questions around how AI will affect scholarly publishing, particularly in regard to managing its use for authors, how to track AI-generated content, where AI content comes from and the ethics around using generative AI in publications. How much of a help or a hindrance generative AI will be remains a hot topic, and this presentation will explore what we know about how these AI models work, how they use published content, the part authors will continue to play and AI’s place in scholarly book publishing today and possibly in the future.